Experimental study on a helium-4 sorption cryocooler. Issue 1 (1st May 2022) - Xi, Xiaotong; Yang, Biao; Gao, Zhaozhao; Chen, Liubiao; Zhou, Yuan; Wang, Junjie
Abstract: The sorption cooler is one of the commonly used Sub-Kelvin temperature refrigeration technologies, used in space exploration and ground experiments to provide a low temperature below 1 K. In this paper, a sorption cooler using helium-4 as the working gas has been developed. At a heat sink temperature of 3 K, the lowest no-load temperature of the developed sorption cooler is 843 mK and the hold time below 1 K is 4 hours. The effects of different sorption pump temperatures and sorption pump cooling rates on the refrigeration performance were studied through experiments. The test results show that during the condensation process, when the temperature of the sorption pump is higher than 45 K, the pump temperature has little effect on the liquefaction efficiency, and speeding up the cooling rate of the sorption pump is conducive to obtaining a lower refrigeration temperature.